University of Illinois Press 2017
DOI: 10.5406/illinois/9780252040320.003.0009
|View full text |Cite
|
Sign up to set email alerts
|

The Macrosociology of Paid Domestic Labor

Abstract: This chapter examines the importance of growing class inequality as a driver of employment growth in paid domestic labor by drawing on macrosociological, rather than microsociological, literature. More specifically, it considers what explains variation in the proportion of the labor force employed in paid domestic labor over time and space. After comparing the microsociology of paid domestic labor with the modernization theory and the macrosociology of domestic labor, the chapter analyzes the 1990 census data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 0 publications
1
20
0
2
Order By: Relevance
“…Finally, the substandard conditions of domestic workers are severely aggravated by the nature of their workplace. Work in a private household fosters social isolation, invisibility and lack of regulation, making domestic workers even more vulnerable to exploitation (Milkman, Reese and Roth, 1998).…”
Section: Non-financial Characteristics and Wage Differentialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the substandard conditions of domestic workers are severely aggravated by the nature of their workplace. Work in a private household fosters social isolation, invisibility and lack of regulation, making domestic workers even more vulnerable to exploitation (Milkman, Reese and Roth, 1998).…”
Section: Non-financial Characteristics and Wage Differentialsmentioning
confidence: 99%
“…Domestic work is a female-dominated occupation, which implies that wages are lower than in occupations normally dominated by men (England, 1992;Perales, 2013). However, gender is not the only issue, as the intersectional approach adopted highlights the manner in which race, citizenship, social origin and migration interconnect to reinforce disadvantages (Milkman, Reese and Roth, 1998). The research found that wage setting in domestic work is far from straightforward.…”
mentioning
confidence: 99%
“…Delegated tasks are clearly devalued and considered "dirty work" (Hughes 1962;Walzer 1984). Outsourcing therefore corresponds to the denial of an equitable division of labor and involves inequalities that are deeper than just income differences (Cohen 1991;Milkman et al 1998;Anderson 2007;Romero 2002;Collins 2006). The service relationship stemming from outsourcing housework is not the result of a straightforward economic exchange between equal individuals, but rather a hierarchic relation between people with different statuses, including in terms of access to citizenship and social benefits (Tronto 2002).…”
Section: Introductionmentioning
confidence: 98%
“…A same correlation between inequalities and frequency of domestic jobs was obtained from a comparison of U.S. cities (Milkman et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Se trata de una ocupación típicamente femenina, con salarios inferiores a los que se perciben en las ocupaciones desempeñadas mayoritariamente por hombres (England, 1992;Perales, 2013). Ahora bien, la interseccionalidad del enfoque adoptado pone de relieve que el género no es la única variable pertinente, sino que un cúmulo de factores interrelacionados (la ciudadanía, el origen social y étnico, la migración) agrava la situación desfavorable del sector (Milkman, Reese y Roth, 1998). Hemos observado que la determinación de los salarios en el trabajo doméstico dista mucho de ser sencilla.…”
unclassified